INNOVATIVE SUSTAINABLE STREETSCAPE DESIGN ALONG KEMBANG JEPUN CORRIDOR SURABAYA - Bambang Soemardiono; Murni Rachmawati; Defry Ardianta; Rahma Sakinah; Muhammad Syafiq; Arie Ranuari; Arina Marta Setya Putri; Deasy Tuffahati (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2017)
Kembang Jepun is an area of the old city of Surabaya known under the name of the Lower Town or